Total Synthesis of (±)-Phaeocaulisin D - Ezzat, Nameer; Bobek, Katelyn; Yuan, Yu (Synlett, 2021)
The tropone sesquiterpene phaeocaulisin D, isolated from the rhizomes of Curcuma phaeocaulis, has previously been shown to inhibit nitric oxide production in macrophages. A total synthesis of phaeocaulisin D was accomplished by using an intramolecular cyclization–dearomatization as a key step. The highlights of the synthesis are effective formation of the 5–7 fused tropone system, and selective methylation of a late-stage intermediate.
Keywords: tropones; dearomatization; sesquiterpenes; medicinal chemistry; total synthesis; phaeocaulisin